Ommatidia of blow fly, house fly, and flesh fly: Implication of their vision efficiency - Kabkaew L. Sukontason (2018)
This work aims to elucidate the number of ommatidia or facets (the outwardly visible units of each ommatidium) for compound eyes in blow flies [Chrysomya megacephala (F.), Chrysomya rufifacies (Macquart), Chrysomya nigripes (Aubertin), Lucilia cuprina (Wiedemann)], house flies (Musca domestica L.), and flesh flies (Liosarcophaga dux Thomson) by manual counts of the corneal spreads. The head of the fly in each species was soaked in 20% potassium hydroxide solution at room temperature for 7 days, and the clear compound eye was dissected into six small parts, each of which was placed onto a slide and flattened using a coverslip. Images of each part were obtained using a microscope connected to a computer. The printed images of each part were magnified, and the total number of ommatidia per eye was manually counted. For males, the mean number of ommatidia was statistically different among all flies examined: L. dux (6,032) > C. rufifacies (5,356) > C. nigripes (4,798) > C. megacephala (4,376) > L. cuprina (3,665) > M. domestica (3,484). Likewise, the mean number of facets in females was statistically different: L. dux (6,086) > C. megacephala (5,641) > C. rufifacies (5,208) > C. nigripes (4,774) > L. cuprina (3,608) > M. domestica (3433). Scanning electron microscopy analysis of adult flies revealed the sexual dimorphism in the compound eye. Male C. megacephala had large ommatidia in the upper two thirds part and small ommatidia in the lower one third part, whereas only small ommatidia were detected in females. Dense postulate appearance was detected in the external surface of the corneal lens of the ommatidia of C. megacephala, C. rufifacies, and C. nigripes, while a mix of dense postulate appearance and variable groove array length was detected in L. cuprina and M. domestica. The probable functions of ommatidia are discussed with reference to other literature. © 2008 Springer-Verlag.